The Internship: Bridge Between Marketplace and Liberal Arts Education in the Catholic Tradition - Grabowsky, Eric; Harden Fritz, Janie M. (Catholic Education: A Journal of Inquiry and Practice, 2007)
Internships can be distinctive pedagogical opportunities within a Catholic liberal arts education. The applied marketplace experience provided by an internship, properly understood, is consistent with the Catholic understanding of education. The value of internships for Catholic higher education can be illustrated by focusing on communication and rhetorical studies. This essay consists of a selected review of literature situating internships within liberal arts education, followed by the articulation of a Thomistic framework for rhetorical education.